Pelatihan Penulisan Karya Ilmiah Kelompok Guru MGMP Bahasa Indonesia di Kabupaten Bojonegoro - Warsiman Warsiman; Wandayani Goeyardi; Lilik Wahyuni; M. A. Haris Firismanda; Endang Sholihatin (IKIP PGRI Bojonegoro, 2022)
ABSTRACTThe ability to write scientific papers for the Indonesian MGMP (subject teacher) group of teachers in Bojonegoro district is low. Various efforts of the Bojonegoro District Education Office in providing upgrading to teachers on scientific writing techniques have not yielded results. The number of teachers who do not understand the technique of writing scientific papers is caused by the low understanding of teachers and the lack of intensity in providing training to write scientific papers. One of the efforts to overcome these problems is the provision of intensive training to teachers on the technique of writing scientific papers. The provision of intensive training is intended to help provide enlightenment in understanding and direct practice of scientific writing techniques. This community service activity is carried out for teachers who are members of the Indonesian Language MGMP teacher group in Bojonegoro district. The method used in this activity is to conduct intensive scientific writing training. As a result of this activity, the ability of teachers who are members of the Indonesian MGMP teacher group in Bojonegoro district has increased significantly. These results can be seen from the ability of teachers to understand and practice scientific writing techniques. Keywords: Training, writing scientific papers, MGMP. ABSTRAKKemampuan menulis karya ilmiah kelompok guru MGMP (musyawarah guru mata pelajaran) Bahasa Indonesia di kabupaten Bojonegoro tergolong rendah. Berbagai upaya Dinas Pendidikan kabupaten Bojonegoro dalam memberikan penataran kepada para guru tentang teknik menulis karya ilmiah belum membuahkan hasil. Banyaknya guru yang belum mengerti teknik menulis karya ilmiah tersebut disebabkan oleh rendahnya pemahaman guru serta kurangnya intensitas pemberian pelatihan menulis karya ilmiah. Salah satu upaya untuk mengatasi permasalahan tersebut adalah pemberian pelatihan secara intensif kepada para guru tentang teknik menulis karya ilmiah. Pemberian pelatihan secara intensif tersebut dimaksudkan untuk membantu memberikan pencerahan dalam memahami dan mempraktikan secara langsung teknik menulis karya ilmiah. Kegiatan pengabdian kepada masyarakat ini dilakukan terhadap para guru yang tergabung dalam kelompok guru MGMP Bahasa Indonesia di kabupaten Bojonegoro. Metode yang digunakan dalam kegiatan ini adalah melakukan pelatihan menulis karya ilmiah secara intensif. Hasil dari kegiatan ini, kemampuan guru yang tergabung dalam kelompok guru MGMP Bahasa Indonesia di kabupaten Bojonegoro mengalami peningkatan signifikan. Hasil tersebut dapat dilihat dari kemampuan para guru memahami dan mempraktikan teknik menulis karya ilmiah. Kata Kunci: Pelatihan, menulis karya ilmiah, MGMP.